Atmospheric chemistry and physics from air pollution to climate change - Seinfeld, John H.; Pandis, Spyros N. 1963- (John Wiley & Sons, Inc., 2016)
A detailed account of the chemistry and physics of the atmosphere - for graduate students, professionals and libraries involved in environmental, civil and chemical engineering projects and studies.